Santal Women and the Rebellion of 1855 in Colonial India. Issue 1 (June 2017) - Mallick, Ata
It is generally assumed that Santal women contributed an imperative role in the Santal rebellion of 1855. According to the judicial records of the rebellion, almost every Santal woman was a rebel and many of them were arrested for their active involvement in the rebellion. Scholars on Santal rebellion have used such colonial administrative accounts to emphasize the subaltern protest against colonialism. However, a detailed study of administrative accounts also reveals that, after trial, most of the women prisoners were released as they were found innocent. Access to insider voices reveals how Santal women were persecuted under the pretext of witch-hunting by the very orders of Santal leaders. This article would argue how the women became the victims of the unrest and how the Santal rebellion was not spontaneous, and would critically propose how the age-old concept of women's participation in the Santal rebellion of 1855 needs reconsideration.